Chemoenzymatic synthesis of 3-deoxy-3-fluoro-l-fucose and its enzymatic incorporation into glycoconjugates. Issue 47 (11th May 2020) - Valverde, Pablo; Vendeville, Jean-Baptiste; Hollingsworth, Kristian; Mattey, Ashley P.; Keenan, Tessa; Chidwick, Harriet; Ledru, Helene; Huonnic, Kler; Huang, Kun; Light, Mark E.; Turner, Nicholas; Jiménez-Barbero, Jesús; et al.
Abstract : A chemoenzymatic synthesis of 3-deoxy-3-fluoro-l -fucose, using a d - to l -sugar translation strategy, and its enzymatic activation and glycosylation, is reported. Abstract : The first synthesis of 3-deoxy-3-fluoro-l -fucose is presented, which employs a d - to l -sugar translation strategy, and involves an enzymatic oxidation of 3-deoxy-3-fluoro-l -fucitol. Enzymatic activation (FKP) and glycosylation using an α-1, 2 and an α-1, 3 fucosyltransferase to obtain two fluorinated trisaccharides demonstrates its potential as a novel versatile chemical probe in glycobiology.